Pengaruh Model Pembelajaran Snowball Throwing dengan Media Rolling Ball Game terhadap Motivasi Belajar Siswa Berbasis Daring dalam Pembelajaran IPS Pada Kelas VIII SMP N 33 Semarang - Putri, Dyah Ayu Sagita; Ginanjar, Asep (Sosiolium: Jurnal Pembelajaran IPS, 2021)
In the global era, it requires world education to always adjust and follow technological development to improve the quality of education, especially are used of varied and creative models and media for education, especially in the learning process. The purpose of this study was to determine the effect of the snowball throwing learning model with rolling ball game media on online-based students learning motivation in social education at the class of VIII SMP N 33 Semarang. The method used in this research is quantitative. The results of this study are (1) The learning implementation uses the snowball throwing learning model and the rolling ball game media at SMP N 33 Semarang. (2) The use of the snowball throwing learning model and the rolling ball game media can have an influence on student learning motivation in social studies learning. (3) There are obstacles, namely the available hardware such as cellphones or laptops and unstable internet networks during learning activities.